2023
DOI: 10.1017/cts.2023.580
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and health disparities: Association between the area deprivation index and primary care telemedicine utilization during the COVID-19 pandemic

Abstract: Introduction: The rapid implementation of telemedicine during the COVID-19 pandemic may have exacerbated the existing health disparities. This study investigated the association between the area deprivation index (ADI), which serves as a measure of socioeconomic deprivation within a geographic area, and the utilization of telemedicine in primary care. Methods: The study data source was electronic health records. The study population consisted of patients with at least one primary care visit between March 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…One key study finding is that patients with breast cancer living in greater socioeconomically disadvantaged neighborhoods were less likely to use telemedicine for care and services, consistent with previous studies of patients in primary care, adult outpatient, and hematology or oncology settings [ 8 , 24 - 28 ]. A descriptive study suggested no correlation between ADI scores and interest in telehealth visits among 64 patients with head and neck cancers (interested: median ADI score=4.0 vs not interested: median ADI score=5.0; P =.79) [ 27 ], but the small sample size limited the reliability of these findings.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…One key study finding is that patients with breast cancer living in greater socioeconomically disadvantaged neighborhoods were less likely to use telemedicine for care and services, consistent with previous studies of patients in primary care, adult outpatient, and hematology or oncology settings [ 8 , 24 - 28 ]. A descriptive study suggested no correlation between ADI scores and interest in telehealth visits among 64 patients with head and neck cancers (interested: median ADI score=4.0 vs not interested: median ADI score=5.0; P =.79) [ 27 ], but the small sample size limited the reliability of these findings.…”
Section: Discussionsupporting
confidence: 79%
“…Neighborhood socioeconomic disadvantage has been shown to negatively affect health outcomes [ 17 , 18 ], access to care and preventive services [ 19 , 20 ], survival outcomes [ 18 , 21 ], and quality of life [ 22 ] among patients with cancer [ 23 ]. Previous investigations have also found neighborhood socioeconomic disadvantage to be associated with a lower likelihood of telemedicine use among patients in primary care and hematology or oncology clinics, as well as among outpatients [ 8 , 24 - 28 ]. A study of 627 patients with cancer experiencing financial distress during the COVID-19 pandemic reported a 3% decrease in the rate of telemedicine use per 10-unit increase in the Area Deprivation Index (ADI) [ 8 ], a validated composite measure of neighborhood-level SES [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ADI was selected because it is the only composite measure available at the census block group level, 21 was designed for use in analyzing mortality 22 and health care outcomes, 19 and has been associated with inequities in telemedicine utilization. 23 An important caveat of composite, census-based measures, such as the ADI, is that prior research evaluating California's “Healthy Places Index” composite measure (which has many similarities with ADI) indicated that this index underrepresented NHPI populations, 24 but there has not, to our knowledge, been a specific measure of neighborhood disadvantage developed and validated for NHPI populations. The Social Vulnerability Index, which includes a measure of race and ethnicity, was not selected because it was designed for disaster management and for larger geographic levels.…”
Section: Methodsmentioning
confidence: 99%
“…Opportunities for DHTs to generate RWD/RWE [15,[21][22][23] Digital health technologies (DHTs) offer a host of opportunities to change how healthcare is delivered, tracked, and disseminated. DHTs are defined by FDA as integrated systems that use computing platforms, connectivity, software, and/or sensors for healthcare.…”
Section: Rwd/rwe To Advance Health Outcomes and Address Health Dispar...mentioning
confidence: 99%